Small anion-assisted electrochemical potential splitting in a new series of bistriarylamine derivatives: organic mixed valency across a urea bridge and zwitterionization - Tahara, Keishiro; Nakakita, Tetsufumi; Starikova, Alyona A.; Ikeda, Takashi; Abe, Masaaki; Kikuchi, Jun-ichi (Beilstein Journal of Organic Chemistry, 2019)
We report the synthesis of a new bistriarylamine series having a urea bridge and investigate its mixed-valence (MV) states by electrochemical and spectroelectrochemical methods. We found that the supporting electrolytes had unusual effects on potential splitting during electrochemical behavior, in which a smaller counteranion thermodynamically stabilized a MV cation more substantially than did a bulky one. The effects contrary to those reported in conventional MV systems were explained by zwitterionization through hydrogen bonding between the urea bridge and the counteranions, increasing the electronic interactions between two triarylamino units. Furthermore, we clarified the intervalence charge transfer characteristics of the zwitterionic MV state.
Keywords: anion binding; electrochemistry; hydrogen bonding; triarylamine; urea; zwitterionic mixed valency